Microbial Biotechnology is 15! An adventure in journal parenting. Issue 1 (30th November 2021) - Timmis, Kenneth; Timmis, Joan
Abstract : This year, 2022, Microbial Biotechnology ( MBT ) celebrates its 15th birthday. In journal terms, 15 is adulthood. It has been a privilege to develop the idea, launch the journal, nurture it in its infancy and stimulate and support it during its adolescence and early adulthood. The success of MBT – its growth over the last 4 years averaging > 30%, and the highest impact factor in the field, making it the leading research journal in applied microbiology/microbial biotechnology and the most attractive to publish in – gives us enormous pleasure and satisfaction, and not a little pride.